Bioinspired hydrogel microfibres colour-encoded with colloidal crystals. Issue 9 (24th June 2019) - Meng, Zhi-Jun; Zhang, Jing; Deng, Xu; Liu, Ji; Yu, Ziyi; Abell, Chris
Abstract : The integration of microfluidic spinning and colloidal crystal microdots enable the colour-encoded hydrogel microfibres with facile and flexible manipulation of the encoding. Abstract : Herein we describe a colour encoding system based on sequentially-encoded colloidal crystal microdots within hydrogel microfibres. This approach exploits a microfluidic spinning technology to generate microfibres in which colloidal crystals, of tuneable size, interval distance, number and sequential array, are orthogonally and simultaneously embedded. The hydrogel microfibre is comprised of calcium alginate, which can gel rapidly, is transparent and soft, and serves as a scaffold for the colloidal crystals. Further, the structural colour of the colloidal crystal microdots is visible and spectroscopically readable, offering a reliable and versatile colour-coding toolbox. We demonstrate the scalability and tuneability of the microfluidic spinning approach for generating hydrogel microfibres that exhibit encoding units from single dot to multiple coloured dots. This paper provides the proof of concept study of developing the application of the colloidal crystals to construct a novel encoding system.